Sistem Pakar Menggunakan Metode Certainty Factor untuk Mengidentifikasi Penyakit pada Hewan Peliharaan - Fortia Magfira; Gunadi Widi Nurcahyo (SEULANGA SYSTEM PUBLISHER, 2020)
Large domesticated types of ruminants such as goats, buffalo and cows are animals that are commonly kept and used as food sources and as assistants to human work in rural areas. Knowledge about pets, especially animal health, is something owners really need to keep their pets healthy. The owner's lack of knowledge about diseases and early handling of diseases in pets and the difficulty of seeing a veterinarian in urgent situations prevent pets from getting proper first aid. This study aims to identify the types of diseases suffered by pets based on the symptoms experienced by pets precisely. The method used is themethod Certainty Factor to accommodate the uncertainty of an expert's thinking on 12 diseases and 47 disease symptoms in pets. The results of this study can identify diseases in pets and produce certainty values ​​for the types of diseases in the form of diseases suffered by pets. So that this research can be a reference in identifying diseases in pets and providing knowledge to owners about first aid and disease management in pets.